THE IDEA OF BLACK FEMINISM IN MAYA ANGELOU’S POEM ‘‘STILL I RISE’’ - Muhammad Haroon Jakhrani (International Journal Of Humanities, Social Sciences And Business (INJOSS), 2023)
This research investigates the idea of black feminism in Maya Angelou's poem "Still I Rise". It used library research to analyse the issues and used black feminism and the ideas of metaphor, simile, symbol, repetition, and tone to analyse the concept of black feminism. The analysis's findings indicate that there is conflict between black women and white people, and that black women would do anything to escape the oppression of both black and white people.